The functional status of patients undergoing surgical treatment for discopathy of lumbar spine - Kołpa, Małgorzata; Zawiślak, Elżbieta; Jurkiewicz, Jurkiewicz; Grochowska, Aneta (Nursing in the 21st Century, 2015)
THE FUNCTIONAL STATUS OF PATIENTS UNDERGOING SURGICAL TREATMENT FOR DISCOPATHY OF LUMBAR SPINEIntroduction. Spinal discopathy due to the recurrent nature of pain is one of diseases which influence the deterioration in the functional status.Aim. The objective of the paper was to assess the severity of pain and functional status of patients with lumbar spine pain syndrome in the period before and after surgery.Material and Methodology. The study included 100 subjects undergoing surgical treatment for discopathy of lumbar spine. In order to check the effects of surgery, VAS scale, RMDQ questionnaire and self-made survey questionnaire were used. Anthropometric measurements were also performed to determine BMI and WHR. The studies were carried out before operation and repeated 6 months after surgery.Results. The sum of pain intensity according to VAS scale in the lumbar spine area, the right and left lower limb was 13.18 (± 3.25 pts) vs. 6.08 (± 2.53 pts) before and after surgery, respectively. Before surgery, the patients achieved on average 11.47 (± 4.56 pts) in RMDQ scale, whereas after treatment this indicator decreased, and the subjects obtained on average 7.31 (± 3.30 pts).Conclusion. After surgical treatment, the functional status of patients improved and the intensity of pain decreased.